ATP Secretion and Metabolism in Regulating Pancreatic Beta Cell Functions and Hepatic Glycolipid Metabolism - Li, Jing; Yan, Han; Xiang, Rui; Yang, Weili; Ye, Jingjing; Yin, Ruili; Yang, Jichun; Chi, Yujing (Frontiers in Physiology, 2022)
Diabetes (DM), especially type 2 diabetes (T2DM) has become one of the major diseases severely threatening public health worldwide. Islet beta cell dysfunctions and peripheral insulin resistance including liver and muscle metabolic disorder play decisive roles in the pathogenesis of T2DM. Particularly, increased hepatic gluconeogenesis due to insulin deficiency or resistance is the central event in the development of fasting hyperglycemia. To maintain or restore the functions of islet beta cells and suppress hepatic gluconeogenesis is crucial for delaying or even stopping the progression of T2DM and diabetic complications. As the key energy outcome of mitochondrial oxidative phosphorylation, adenosine triphosphate (ATP) plays vital roles in the process of almost all the biological activities including metabolic regulation. Cellular ATP participates intracellular energy transfer in all forms of life. Recently, it had also been revealed that ATP can be released by islet beta cells and hepatocytes, and the released ATP and its degraded products including ADP, AMP and adenosine act as important signaling molecules to regulate islet beta cell functions and hepatic glycolipid metabolism via the activation of P2 receptors (ATP receptors). In this review, the latest findings regarding the roles and mechanisms of intracellular and extracellular ATP in regulating islet functions and hepatic glycolipid metabolism would be briefly summarized and discussed.